Case Report: Ophthalmic and associated systemic disorders in free-ranging giant otters (Pteronura brasiliensis) documented through video frames and photographs - Soresini, Grazielle; Foerster, Nathalie; Somma, André T.; da Silva, Fabiano A.; Ribas, Carolina; Leuchtenberger, Caroline; Mourão, Guilherme (Frontiers in Mammal Science, 2025)
The present study aims to report the occurrence of ophthalmic and associated systemic disorders in giant otters (Pteronura brasiliensis) from the Brazilian Pantanal. This mustelid species is classified globally as Endangered and faces increasing threats from various human activities and diseases from domestic animals across most of its range, including Brazil. Over a 10-year period, we recorded 12 wild giant otters showing signs of ophthalmic diseases, as well as other systemic abnormalities. In this study, we describe the ocular conditions based on an analysis of digital-video frames and photographs, discuss potential causes, and highlight the concern that the long-term survival of the giant otter population in a specific area of the southern Brazilian Pantanal may be at risk.